Risk assessment of human-to-human transmission of severe fever with thrombocytopenia syndrome virus based on 10-year clustered analysis - Zhang, Nannan; Mu, Xiaodong; Liu, Jingyu; Liu, Tao (Frontiers in Public Health, 2024)
Background Severe fever with thrombocytopenia syndrome (SFTS) is an acute infectious disease, which was first reported in 2009 in China. Previous studies have rarely quantitatively assessed the transmission and fatal risk of SFTS clusters. Methods Epidemiological information regarding SFTS clusters in Yantai city of Shandong province during 2013-2022 was obtained from the National Public Health Emergency Event Surveillance System (PHEESS) for Disease Control and Prevention information system. The secondary attack rate (SAR) and relative risk (RR) were used to assess the risk of human-to-human transmission of SFTS. Results A total of 20 SFTS clusters involving 51 laboratory-confirmed patients were reported between 2013 and 2022 in Yantai city, Shandong province. Most of the clusters occurred from May to October, and the patients were mainly distributed in four counties. Contact with blood or other fluids [RR = 14.06, 95% confidence interval (CI) = 3.29–70.65, p < 0.001] and using no personal protection equipment (PPE) [11.63% (10/86) vs. 2.22% (2/90), RR = 5.74, 95% CI = 1.17–55.44, p = 0.013] were significantly related with an increased risk of SFTS virus (SFTSV) transmission. Conclusion Our study may provide direct guidance on health education and behavioral interventions for the accompanying relatives and personnel of SFTS patients, both during their hospital stay and upon returning home after discharge.